A Subtitling analysis of Noun Phrase found in "Thor 2: The Dark World" Movie by Josephermlase - Welasih, Pethit; , Dr. Dwi Haryanti, M.Hum; , Dra. Malikatul Laila, M.Hum (2015)
The research studies about the subtitling analysis of noun phrase in Thor 2: The Dark World movie. The objectives of the study are to identify the subtitling variations of noun phrase and to describe the readability of translation in Thor 2: The Dark World movie and its subtitling. The research paper applies descriptive qualitative research. The data of the research are subtitling variations of noun phrase and readability questionnaire. The researcher uses documentation method in collecting the data of noun phrases from English and Indonesian subtitle also interviewing the readers to get the information related to the subtitle. The researcher also used comparison method to analyze the data taken from both subtitles. The results of the research present that first the researcher finds 46 subtitling variation in Indonesian, they are; NP1 (N + PP) translated into NPF (N + AP) and Verb, NP2 (Adj + N) translated into NPA, B, F (N + N, N + Adj, and N + AP) and Adjective, NP3 (Demonstrative + N) translated into NPC, E (N + Adv, N + demonstrative), Noun and Suffix, NP4 (Article + N) translated into NPE (N + Demonstrative), Noun, Verb, Adjective, and Demonstrative, NP5 (Quantifier + N) translated into NPC (N + Adv) and Noun, NP6 (Possessive + N) translated into NPA, D1, D3, i (N + N + N + Pron1, N + Pron3, Particle + N), Noun, Verb, Adjective, Adverb, and Sentence, NP7 (Article + Adj + N) translated into NPB, F, J (N + Adj, N + AP, Numeralia + N + Adj), Verb and Adjective, NP8 (Article + N + N) translated into NPG (N + N + Adj) and Verb, NP9 (Possessive + Adj + N) translated into NPB, H (N + Adj, N + Adj + Pron1) and Noun, NP10 (Article + Adj + N + PP) translated into NPK, L (N + N + N, N + N + Adj + Adv) and Noun, NP11 (Quantifier + Article + N) translated into Verb and Adjective, NP12 (Possessive + Possessive + N) translated into NPA (N + N) and Noun, NP13 (Article + Quantifier + Adj + N) translated into NPF (N + AP) and Verb Phrase. Second, the researcher found 2 levels of readability translation in Thor 2: The Dark World movie. From 370 data, there are 354 data or 95,7% which are categorized as high readability level and 16 data or 4,3% which are categorized as medium readability level